Two-parameter J-A concept in connection with crack-tip constraint. (December 2017) - Matvienko, Yu.G.; Nikishkov, G.P.
Highlights: Two-parameter J - A approach in elastic-plastic fracture mechanics is discussed. The constraint parameter A for various configurations of specimens is computed. The unified JC - A master curve is constructed. Relationship between the crack-tip constraint parameters is analyzed. Abstract: The paper presents theoretical and numerical aspects of the two-parameter J - A approach in elastic-plastic fracture mechanics in connection with crack-tip constraint. This approach is based on the three-term asymptotic expansion for the stress field near the tip of mode I crack in an elastic-plastic solid. It is shown that the parameter A can be introduced in fracture criterion as a constraint parameter. The constraint parameter A and the J -integral for various configurations of standard specimens and the hardening exponent is computed by means of three-dimensional elastic-plastic stress analyses employing finite element method. The magnitude of the constraint parameter A decreases (higher constraint) with the increase of relative specimen thickness. The unified JC - A master curve is constructed for different geometry and thickness of specimens. The two-parameter J - A fracture criterion allows estimating whether elastic approach is conservative or non-conservative. Relationship between the crack-tip constraint parameters A, A 2, Q and S ¯ p of elastic-plastic fracture mechanics is investigated.